1995
DOI: 10.1016/0092-8674(95)90097-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV nuclear import is governed by the phosphotyrosine-mediated binding of matrix to the core domain of integrase

Abstract: The karyophilic properties of the viral matrix (MA) protein govern HIV nuclear import in nondividing cells such as macrophages. A critical regulator of this process is the C-terminal tyrosine phosphorylation of MA during virus maturation. Here, we reveal the mechanism of this phenomenon, by demonstrating that tyrosine phosphorylation induces the binding of MA to integrase (IN). This leads to the incorporation of MA molecules into virus cores, and subsequently into uncoated viral nucleoprotein complexes. A dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
273
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(287 citation statements)
references
References 27 publications
8
273
2
1
Order By: Relevance
“…HIV-1 proviral constructs. The X4-tropic proviral constructs R8 and Nefdefective R8⌬N were described previously (28). R8-based chimeras R8BaL and R8AD8 express the Env genes of the R5-tropic isolates BaL and AD8.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-1 proviral constructs. The X4-tropic proviral constructs R8 and Nefdefective R8⌬N were described previously (28). R8-based chimeras R8BaL and R8AD8 express the Env genes of the R5-tropic isolates BaL and AD8.…”
Section: Methodsmentioning
confidence: 99%
“…22 Unlike retroviruses, lentiviruses are capable of transducing quiescent cells. 23 For HIV, this process appears to be facilitated by the following viral proteins: (1) the integrase protein, 24,25 (2) the matrix protein from gag, 26 (3) the accessory protein vpr 27 and (4) the central polypurine tract (cPPT). 28 As a result of their capacity to transduce nondividing cells -although for some cell types, progression through the cell cycle from G0 to G1b is necessary for efficient, complete reverse transcription of the viral genome 29 -lentiviral vector development has received much interest.…”
Section: Lentivirus-based Vectorsmentioning
confidence: 99%
“…The predominant phosphoamino acids in these proteins were phosphoserine and/or phosphothreonine. Tyrosine phosphorylation of retroviral protein was recently demonstrated in HIV matrix protein (MA) [12] and it was shown that a direct interaction between tyrosine-phosphorylated MA and the central domain of the integrase governed the HIV nuclear import [13].…”
Section: Introductionmentioning
confidence: 99%